Applications of Silicon Photonics in Sensors and Waveguides - Narayana Deepak Kallepalli, Lakshmi (IntechOpen, 2018)
This book is a collection of five original research articles on silicon photonics. The discussed issues are organized into two parts. Part 1 describes the science behind the silicon photonics emphasizing the role of photonic circuits on silicon, and Part 2 describes applications in waveguide and optical transmissions. This book should be of interest to academic researchers and engineers. The chapters included are fundamental science and applications of silicon photonics, optical properties of thin nanocrystalline silicon films, microporous silicon in gas sensing, Mach-Zehnder interferometer cell-based silicon waveguide, experimental study of porous silicon films, and integrated optical switches and their applications.